2016
DOI: 10.1002/2015jb012325
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure beneath the Northern Transantarctic Mountains and Wilkes Subglacial Basin: Implications for tectonic origins

Abstract: The Transantarctic Mountains (TAMs) are the largest noncollisional mountain range on Earth. Their origin, as well as the origin of the Wilkes Subglacial Basin (WSB) along the inland side of the TAMs, has been widely debated, and a key constraint to distinguish between competing models is the underlying crustal structure. Previous investigations have examined this structure but have primarily focused on a small region of the central TAMs near Ross Island, providing little along‐strike constraint. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 61 publications
(166 reference statements)
6
31
1
Order By: Relevance
“…Further, assuming an average crustal thickness of ∼38 km beneath the coastal stations, as suggested by Hansen et al . [], the anisotropic layer could extend roughly from 39 to 264 km in the upper mantle. Unlike the East Antarctic stations, where the anisotropic signature appears to be concentrated in the cratonic lithosphere, the depth extent of the anisotropic signature along the Ross Sea coastline constrains the anisotropy within the lower‐viscosity, higher‐temperature asthenosphere.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Further, assuming an average crustal thickness of ∼38 km beneath the coastal stations, as suggested by Hansen et al . [], the anisotropic layer could extend roughly from 39 to 264 km in the upper mantle. Unlike the East Antarctic stations, where the anisotropic signature appears to be concentrated in the cratonic lithosphere, the depth extent of the anisotropic signature along the Ross Sea coastline constrains the anisotropy within the lower‐viscosity, higher‐temperature asthenosphere.…”
Section: Discussioncontrasting
confidence: 98%
“…More recently, the Transantarctic Mountains Northern Network (TAMNNET) was deployed in Northern Victoria Land to expand seismic investigations of the TAMs (Figure ) [ Hansen et al ., ]. Similar to TAMSEIS, little evidence for a thick crustal root is observed beneath the TAMNNET array [ Hansen et al ., ]. Further, both surface [ Graw et al ., ] and body wave [ Brenn , ] tomography models generated with the TAMNNET data indicate a previously unidentified low velocity anomaly beneath the northern TAMs.…”
Section: Previous Seismological Investigationsmentioning
confidence: 99%
“…Alternatively, it has been suggested that volcanism in the EVP and the slow seismic velocities beneath Ross Island result from localized, rift-related decompression melting associated with the Terror Rift (Wannamaker and Stodt, 1996;Rocchi et al, 2005;Karner et al, 2005;Bialas et al, 2007;Huerta and Harry, 2007). Mantle flow may have been directed toward the East Antarctic craton, thereby warming the cratonic lithosphere, and Cenozoic reactivation of Paleozoic tectonic discontinuities may have resulted in localized decompression melting (Rocchi et al, 2003(Rocchi et al, , 2005Storti et al, 2007;Nardini et al, 2009).…”
Section: Low Velocity Zone Sourcesmentioning
confidence: 95%
“…Instead of a thermal load, this uplift mechanism requires a thick crustal root beneath the TAMs to provide isostatic buoyancy (Studinger et al, 2004;Karner et al, 2005). Other studies have also advocated for a crustal root, possibly resulting from the extensional collapse of thickened crust in West Antarctica (Bialas et al, 2007;Huerta and Harry, 2007). Alternatively, Lawrence et al (2006), who jointly inverted Pwave receiver functions with Rayleigh wave phase velocities, suggested a hybrid model that includes a combination of erosional unloading, thermal buoyancy, and local crustal isostasy.…”
Section: Introductionmentioning
confidence: 92%
“…Gravity modeling, seismic refraction surveys, and body and surface wave studies show that the crust thickness varies from 10–21 km in the basins up to 24 km beneath the basement highs (Bannister et al, 2003; Behrendt, 1999; Danesi & Morelli, 2000; Davey, 1981; Davey & Brancolini, 1995; Guterch et al, 1985; Llubes et al, 2003; Ritzwoller et al, 2001; Trey et al, 1999). The crust is thicker on the flanks of the rift, ranging from 25–30 km in Marie Byrd Land on the east and from 35–40 km beneath the Transantarctic Mountains on the west (An et al, 2015; Bannister et al, 2000; Busetti et al, 1999; Chaput et al, 2014; Finotello et al, 2011; Graw et al, 2016; Hansen et al, 2009, 2016; Lawrence et al, 2006; Llubes et al, 2003; O'Donnell & Nyblade, 2014; Pyle et al, 2010; Studinger et al, 2006; Winberry & Anandakrishnan, 2004). Comparison of the modern crust thickness in the Ross Sea basins with estimated prerift thickness, as well as plate reconstructions, suggests that the region has widened by 25% to 50% (250–500 km) since the Late Cretaceous Period (Behrendt, 1999; Davey & Brancolini, 1995; Decesari, Wilson, et al, 2007; D. S. Wilson & Luyendyk, 2009).…”
Section: Geology Of the Vlb And Warsmentioning
confidence: 99%